Effect of Fe–N modification on the properties of biochars and their adsorption behavior on tetracycline removal from aqueous solution - Mei, Yanglu; Xu, Jin; Zhang, Yin; Li, Bin; Fan, Shisuo; Xu, Huacheng (Bioresource technology, 2021)
[Display omitted] •Fe–N co-modification on the characteristicsof biochar was investigated.•The maximum capacity of TC adsorption on Fe-N-RSBC can reach 156 mg·g−1.•The iron oxide nanoparticles in Fe-N-RSBC include γ-Fe2O3, Fe3O4 and Fe3C.•The adsorption mechanisms involve pore filling, H-bond, and surface complexation. Tetracycline (TC) adsorption capacity on pristine biochar was limited. Biochar modification can greatly improve its adsorption amount. In this study, rice straw was mixed with FeCl3·6H2O and urea to prepare a Fe–N modified biochar via a one-pot pyrolysis method at 700 °C. Meanwhile, pristine biochar (RSBC), urea modified biochar (N–RSBC), FeCl3·6H2O-modified biochar (Fe–RSBC) were produced as control. More functional groups, more graphited carbon structure, and magnetic components were observed in Fe–N–RSBC. Compared with RSBC, the surface area, total pore and micropore volume of Fe–N–RSBC increased 3.4-fold, 3.0-fold and 2.3-fold, respectively. The maximum capacity of TC adsorption on Fe-N-RSBC reached 156 mg·g−1, which was 5.4 − fold, 8.2 − fold and 1.9 − fold increase to that of RSBC, N-RSBC, Fe-RSBC, respectively. The mechanism of TC adsorption on Fe-N-RSBC involved pore filling, hydrogen-bondinteraction, surface complexation, and π–π interaction. Therefore, Fe-N-RSBC can be used as an effective adsorbent for TC removal from aqueous solution.